Factors And Motivations For Female Muslim Entrepreneurs In Ghana: A Case Study Of Selected Muslim Female Entrepreneurs In Ashaiman - Mustapha Abdullah Kuyateh (Penerbit Hellow Pustaka, 2025)
Female entrepreneurship in Ghana is a practice which scholars have explored severally in recent years. Just as many other countries, the role of Ghanaian Muslim women has been undermined for a longer period. However, the 20th century marked a positive turn in Ghanaian culture. The rate of discrimination and seclusion of women from economic empowerment started reducing significantly. Today, Ghanaian women are struggling to compete effectively with their male counterparts in entrepreneurial sector. The purpose of having women empowerment on the market economy is to generate more income to the country. Also, the practice lessens the rate of unemployment and high rate of dependency in Ashaiman. Hence, it is apparent that the entrepreneurial actions in Ashaiman are motivated by a number of factors that are presented in the paper. From the study of the influential factors and motivation for female Muslim entrepreneurs in Ashaiman, it has been noted that the process of entrepreneurship among the current female entrepreneurs in the country can be categorized as either passive or initiative. While looking at the passive entrepreneurship among the female entrepreneurs, it is noted that those people are driven by the daily needs of their families. On the other hand, initiative entrepreneurship relies much more on human capital and social capital. The zeal and motivation that they possess lead them to developing far-sighted enterprises, hence contributing to the economic development of the country.